Characteristics of canine oral tumors: Insights into prevalence, types, and lesion distribution - Satthathum, Chakkarin; Srisampane, Supreeya; Jariyarangsrirattana, Pollawat; Anusorn, Pitak; Sattasathuchana, Panpicha; Thengchaisri, Naris (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The escalating prevalence of canine oral tumors has emerged as a considerable health concern. This study examined the prevalence, types, and distributions of lesions linked to canine oral tumors. Material and Methods: The medical records of 526 dogs diagnosed with oral tumors were analyzed to determine the prevalence, types, and distributions. Tumor stages were classified into four categories using the tumor node metastasis system. Results: Among the 526 dogs, there were 118 cases of benign tumors and 408 cases of malignant tumors. Acanthomatous ameloblastoma was the most common benign tumor (43.22%), while melanoma was the most common malignant tumor (51.23%). The gingiva was the most common site for both benign and malignant lesions, accounting for 89.83% and 63.73% of cases, respectively. Melanoma, squamous cell carcinoma, and fibrosarcoma were primarily located in the gingiva, whereas osteosarcoma was commonly found in the mandible. Most tumors were classified as stage III (ranging from 46.84% to 74.58%). Of the reported cases, 56.08% were males and 43.92% were females, and the most common breed was mixed at 30.41%, followed by Poodle at 14.25% and Shih Tzu at 11.40%. Moreover, patients with malignant oral tumors (11.6 ± 3.1 years) were significantly older than those with benign tumors (8.9 ± 3.4 years, p < 0.0001). Conclusion: Gingiva was the primary site for oral tumors, and mainly classified as stage III. These findings emphasize the increasing occurrence of oral tumors in senior and geriatric dogs and provide insights into the prevalent types and distribution. J. Adv. Vet. Anim. Res., 10(3): 554–562, September 2023 http://doi.org/10.5455/javar.2023.j709